The Influence Of Profitability Ratio, Leverage and Capital Intensity Ratio on Tax Avoidance Practices In Manufacturing Companies Listed On The IDX For The Period 2016-2020 - Tangkas Putra Kencana; Tutut Dewi Astuti (Lembaga Riset dan Inovasi Al-Matani, 2023)
Tax avoidance practice is the act of organizing financial or business transactions to reduce tax liabilities legally without violating applicable tax laws. Testing the effect of profitability, leverage, and capital intensity ratio (CIR) on tax avoidance practices is the purpose of this study. The object of this research was conducted in the basic and chemical sub-sector manufacturing industries listed on the IDX in the 2016-2020 period. The sample used was 70 companies for five years with 184 companies observed. The technique of taking the sample uses purposive sampling whose method uses multiple linear regression. The type of data is secondary data such as financial and annual reports downloaded from the idx.co.id page and the company's official website. The results of this study show that the variables of profitability, leverage, and capital intensity have a positive influence on tax avoidance practices.